Catalytic Pyrolysis of Plastic Waste for Gasoline Fuel: Reaction Mechanism Engine Integration - Enzo Wiranta Battra Siahaan; Tulus Burhanuddin Sitorus; Himsar Ambarita; Taufiq Bin Nur; Ilmi Ilmi; Janter Pangaduan Simanjuntak (Universitas Muhammadiyah Magelang, 2025)
The escalating accumulation of plastic waste demands not only scalable but integrative conversion solutions. Among thermochemical routes, catalytic pyrolysis has emerged as a promising pathway to produce gasoline-range hydrocarbons from plastic polymers compatible with spark-ignition engines. This review critically evaluates recent advancements in pyrolysis of key plastics polypropylene (PP), polyethylene (PE), polystyrene (PS), polyethylene terephthalate (PET), and polyvinyl chloride (PVC) with a focus on fuel yield, hydrocarbon distribution, and engine-level performance. Comparative analysis reveals PP as the most viable feedstock, achieving up to 85% liquid yield and producing oil with high Research Octane Numbers (RON 85”“95), outperforming PE and PS in combustion efficiency and emission compliance. However, persistent challenges such as fuel instability, catalyst deactivation, and elevated aromatic emissions particularly from PS complicate real-world deployment. The review further dissects the interplay between catalyst type, reactor design, and post-treatment, highlighting how these variables modulate product quality and engine operability. Notably, 10”“20% PP/PE-derived pyrolysis gasoline blends demonstrate near-parity with conventional gasoline in Brake Thermal Efficiency and regulated emissions, without requiring engine modifications. This work bridges molecular-level reaction chemistry with combustion diagnostics and policy-aligned emission metrics, offering a rare multiscale synthesis. By articulating process-emission-performance trade-offs, it provides a strategic reference for researchers and practitioners aiming to scale waste-to-fuel systems within circular economy frameworks.